Transition Pathways towards a Sustainable and Carbon-Neutral Economy in Finland by 2035 - Alahakoon Arachchige, Kalpani (My University, 2025)
The planet is warming at an unprecedented rate, primarily due to increasing atmospheric carbon dioxide (CO2) concentrations from anthropogenic activities that adversely impact the climate system. Climate change has severe manifestations, affecting human populations, ecosystems, and economies worldwide. Hence, pursuing alternative transition pathways for achieving carbon neutrality should be viewed not merely as a future goal but as a critical necessity to protect planetary health and ensure humanity’s survival. The aims of this study are twofold. First, to conceptualise a carbon-neutral, sustainable economy in Finland by 2035, reflecting the preferences of economically focused green political actors; and second, to develop alternative transition pathways to guide future outcomes toward this preferred vision. Employing a critical and normative framework, the study uses Backcasting through Futures workshops to engage participants in envisioning preferred futures and viable transition pathways. It simultaneously cultivates future-oriented thinking skills among society, fulfilling one of the responsibilities of the futurist. The research identifies key findings, including four distinct preferred future scenarios of a carbon-neutral economy: ‘Silver Bullet’, a technology-driven model; ‘Progression’, emphasising resource conservation; ‘Sustainable Dream World’, advocating for degrowth and social responsibility; and ‘Back to Nature’, promoting nature-based self-sufficiency. Furthermore, the findings indicate that the proposed transition pathways with policy measures do not adhere to a singular or linear trajectory; rather, they encompass a range of synergistic and interactive policy bundles, including basic income, resource taxation, and educational reforms. The discussion reviews the findings through scenario archetypes and transition archetypes in the literature, insights gained from Dator’s generic futures and Multi-Level Perspective (MLP) framework. The scenario archetypes establish a linkage to concepts such as “Transformation,” “Collapse,” and “Disciplined Society,” asserting that these preferred visions pose a challenge to the dominant growth-centric paradigm while advocating for a fundamental reorientation beyond conventional economic growth notions. Additionally, the theoretical framework of transition archetypes, drawn from the MLP, illustrates the relevance of a “Mixing Pathways” approach, characterised by the co-evolution of “Transformation,” “Reconfiguration,” “Technological Substitution,” and “De-alignment/Re-alignment.” This reflects the need for multiple pathways, emphasising the complex realities inherent in the pursuit of transitioning towards a carbon-neutral economy.
Keywords: Carbon neutral economy, preferred scenarios, transition pathways, Multi-Level Perspective, Backcasting, Futures Workshops